CHARACTER BUILDING THROUGH ISLAMIC EDUCATION: NURTURING THE INDONESIAN NATION'S VALUES - Mohamad Madum; Daimah Daimah (LP2M Universitas Ibrahimy, 2024)
The current moral decline of students is very worrying, even though the essence of education is to increase moral values. The government has implemented several policies to address this issue. However, the visible changes have not yet materialized, underscoring the critical role of Islamic education in shaping character education for the Indonesian nation. This study aims to learn about Islamic education from the perspective of character education for the Indonesian people. The research method used is literature research, which involves searching for and viewing data related to themes, types, and research approaches. The researchers divide the qualitatively descriptive data into primary and secondary categories for subsequent analysis from the correct perspective. The results of this study indicate that Islamic education has several concepts for shaping the character of Indonesian students in accordance with the long-term plans of the Indonesian nation. Furthermore, Islamic education exemplifies character education by drawing on the example of the Prophet Muhammad PBUH. This article concludes that Islamic education in shaping students' character is following the objectives of character education in Indonesia as stated in the 2005–2025 National Long-term Development Plan.